Comparing Minimum Wage Policies in East Asia: Political Competition and Labor Incorporation. Issue 2 (4th March 2023) - Wong, Mathew Y. H.
Abstract: This article attempts to explain the evolution of minimum wage levels in three East Asian economies: Japan, South Korea, and Taiwan. A political-economic framework incorporating the levels of political competition and labor incorporation is suggested. With strong political competition and a lack of labor incorporation, South Korea exhibits the strongest minimum wage increase, followed by Taiwan with incorporated labor. Japan has the weakest minimum wage with uncompetitive politics and labor incorporation. The framework is supported by descriptive accounts of the three cases and supplemented by quantitative analysis. As a factor commonly viewed as less relevant for welfare development in the region, the impact of leftist governments is found to be conditional upon the level of political competition. This article contributes to the literature by providing a political-economic explanation of the minimum wage, as well as linking East Asia with the mainstream welfare state literature.